(untitled) (Fiep Bulletin - online, 2013)
Rheumatic diseases, including Rheumatoid Arthritis (RA) are associated with a series of events, especially stiffness, pain, deformity and articulate soft tissue, muscle atrophy, unconditioned and widespread decline in physical function. Resistance exercises (RE) are of great importance to these symptoms do not affect the activities of daily living, as stimuli to promote physical fitness, such as: flexibility, strength development, strength and power. The study aimed to verify the influence of RE in the development of strength, flexibility, quality of life and indicators of the disease in patients with RA. The methodology of this study is based on the participation of six women aged over 18 years. Subjected to RE, twice weekly, with intervals of at least 48 hours between training sessions for 23 weeks. All the participants signed the free and informed consent and the project was approved by the Ethics Committee of FHCGV (Protocol No. .068/2006). Initially it was made assessing the quality of life and physical fitness test and there are indicators of disease through clinical and laboratory examinations. Subsequently, RE was applied according to the needs of participants. According to the nature of the variables (numerical continuous) found through the Z test score, was used descriptive statistical analysis, informing the percentage of the results, as mean and standard deviation (SD) of each variable. For analysis of statistical significance was used Student’s t test for paired samples. The study acknowledged the value of p <0.05 for statistical significance, held in Software BioEstat 4.0. The results of this study demonstrate the efficiency of RE in patients with RA, especially with regard to flexibility (p = 0.0054), to force manual (p = 0.5197, p = 0.5286) and lower limbs (p <0023). Were reported improvements in activities of daily life, showing great relevance in the life of them.